Factors that motivate Mappakasunggu women of seaweed farmers to develop a family economic survival strategy - Subair, Nurlina; Haris, Risma (Aquaculture, Aquarium, Conservation & Legislation, 2019)
Survival strategy is important for farmers in seaweed cultivation due to waves that often disrupt their economic activities. The farmers will be usually looking for alternative jobs or additional livelihood. In a bad condition, the women of seaweed farmers should also be ready to be able to share the role in earning a living to meet the economic needs of the household. So, the purpose of this research is to describe the factors causing women of seaweed farmers to do survival strategy and what strategy is used to solve family economic problems. This research was conducted at Mappakasunggu in Takalar regency, the South Sulawesi Province-Indonesia between July and September 2017. Subjects in this research were five individual female household members of seaweed farmers. This research is a qualitative research with case study method, the data collection techniques using purposive sampling, the method of in-depth interview and participant observation especially to obtain data from female individuals who become unit of the case while the focus of data analysis is done by revealing the biography (life history) and interpretation of meanings behind the survival process of women traveled. Results found the factors that cause women seaweed farmers to do survival strategy that is because it has a low-income level and as a single breadwinner while survival strategy taken by women seaweed farmers are (a) to work on farming (b) to own small shop at home, (c) to process seaweed food industry, (d) to farm salt, and (e) to collect and sell seaweed.